“MAKING-OF” – SUCCESSFULLY PLANNING AND IMPLEMENTING PEER-TO-PEER LECTURE FILMS - Pfennig, Anja; Maier-Rothe, Jörg (PEOPLE: International Journal of Social Sciences, 2019)
Recently films have been implemented in higher education as additional audio and visual stimulus. Students like to work with lecture films which cover different learning methodologies. If videos are analogous to the desired learning outcomes of the lecture they are considered a reinforcement, rather than a replacement for lectures. However, filming a lecture and providing this as a video lecture is not meant by a lecture video that covers science on short sequences. To interest students` and become a seriously accepted learning material lecture films need to be of a certain standard. Videos on material science are successfully embedded in “inverted classroom” teaching scenarios for mechanical and automotive engineering students at HTW Berlin in their first year. Initially encouraged by students a set of lecture videos is produced during a one term semester project each semester by 3rd year students (peer-to-peer approach). The “making-of” is attended carefully by lecturers and film experts. But, the peer-to-peer approach is very important only then students` needs, learning approach and individual perspective on teaching material is first hand included in the videos. Because we find lecturers very interested in our approach and at the same time certain aspects have to be taken into account to successfully prepare peer-to-peer lecture films we practically contribute to the most important aspects to start and succeed in the “making-of” of lecture videos.